Identification of critical process parameters and its interplay with nanosuspension formulation prepared by top down media milling technology – A QbD perspective. (June 2013) - Ghosh, Indrajit; Schenck, Daniel; Bose, Sonali; Liu, Frances; Motto, Michael
<x xml:space="preserve">Abstract</x> The purpose of this study was to optimize the process parameters of a poorly soluble drug by top down media milling process using different polymer systems. Process parameters including agitation rate (RPM), size of grinding media and drug content were studied through a Quality by Design (QbD) approach, using three different polymeric stabilizers (HPMC 3 cps, PVP K-30 and HPC-EXF) with the addition of Vitamin E TPGS as a surface active agent. From the statistical analysis, the RPM of the media milling was determined to be the most significant process parameter with respect to influence on particle size. The effects of varying the size of grinding media or drug content were not found to be as significant as the effects of RPM. Finally, the polymeric stabilizer played an important role in the production of nanoparticles. Among the different polymers, HPMC stabilized systems demonstrated superior results with regards to the consistency in producing successful nanoparticles and inhibition of crystal growth during storage. This study established the interplay among the formulation parameters in order to select the design space, which helped us in the identification and rank ordering of critical and noncritical variables related to the quality attributes of nanosuspension formulation during the early phase of product development.